VERSTEK DECISION POWER ON UNDER-HANDS SELLING WHICH THE SELLER DOESN'T EXIST - Ratna Khairani; Rahmida Erliyani; Anang S hophan Tornado (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The transfer of land rights is the transfer of land rights from the old right holder to the new right holder according to the provisions of the applicable laws and regulations. Land law in Indonesia requires the transfer of land rights to be carried out before the Land Deed Official (PPAT), because basically buying and selling land must meet clear and cash requirements. Government Regulation Number 24 of 1997 Concerning Land Registration in Article 37 paragraph (1) states that